2016
DOI: 10.1186/s13058-016-0746-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between mammographic density, tissue microvessel density, and breast biopsy diagnosis

Abstract: BackgroundWomen with high levels of mammographic density (MD) have a four- to six-fold increased risk of developing breast cancer; however, most neither have a prevalent tumor nor will they develop one. Magnetic resonance imaging (MRI) studies suggest that background parenchymal enhancement, an indicator of vascularity, is related to increased breast cancer risk. Correlations of microvessel density (MVD) in tissue, MD and biopsy diagnosis have not been defined, and we investigated these relationships among 218… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…This study also reported that MVD as assessed by CD31 or CD34 might be a better prognostic factor than Factor VIII (Uzzan et al, 2004). A more recent study showed that increased MVD of CD31 in whole sections of breast biopsies was significantly associated (OR =1.69, 95% CI=1.17-2.44) with in situ or invasive breast cancer (Felix et al, 2016). However, in our study, MVD as measured by expression of CD31 was not a significant prognostic factor for overall survival in the 92 patients.…”
Section: Discussionsupporting
confidence: 52%
“…This study also reported that MVD as assessed by CD31 or CD34 might be a better prognostic factor than Factor VIII (Uzzan et al, 2004). A more recent study showed that increased MVD of CD31 in whole sections of breast biopsies was significantly associated (OR =1.69, 95% CI=1.17-2.44) with in situ or invasive breast cancer (Felix et al, 2016). However, in our study, MVD as measured by expression of CD31 was not a significant prognostic factor for overall survival in the 92 patients.…”
Section: Discussionsupporting
confidence: 52%
“…Details of the BREAST Stamp Project and study eligibility characteristics have been described previously. 25,29,32 Eligible participants were women aged 40–65 years referred for image-guided biopsy who did not have breast implants, had not been diagnosed with breast cancer or received cancer treatments, had not undergone breast surgery within one year and had not received chemoprevention. During the enrollment period, mammography registry data indicated that 1227 patients met these eligibility criteria.…”
Section: Methodsmentioning
confidence: 99%
“…29 The distribution of the collected breast cancer risk factor information, including the demographic and lifestyle characteristics of the enrolled BREAST Stamp study population, has been previously described. 25,29,32 Details of the analytical population included in this current analysis are outlined in more detail below and described in Table 1. The Institutional Review Boards at the NCI and the University of Vermont approved the protocol for this project for either active consenting or a waiver of consent to enroll participants, link data and perform analytical studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, by virtue of the deep learning process, it is unclear what components of the stroma may be driving the machine classifier. Additional studies are needed to understand the biology of the stroma surrounding ductal carcinoma in situ, including the role of the vasculature, which we previously showed was increased in ductal carcinoma in situ versus benign biopsies from this study, with the highest microvessel density in invasive carcinoma 45 . Further experiments on larger cohorts of ductal carcinoma in situ with long-term clinical follow-up are needed, to study the potential that stromal features may have prognostic value.…”
Section: Discussionmentioning
confidence: 68%